Feeling the Beat: Bouncing Synchronization to Vibrotactile Music in Hearing and Early Deaf People - Tranchant, Pauline; Shiell, Martha M.; Giordano, Marcello; Nadeau, Alexis; Peretz, Isabelle; Zatorre, Robert J. (Frontiers in Neuroscience, 2017)
The ability to dance relies on the ability to synchronize movements to a perceived musical beat. Typically, beat synchronization is studied with auditory stimuli. However, in many typical social dancing situations, music can also be perceived as vibrations when objects that generate sounds also generate vibrations. This vibrotactile musical perception is of particular relevance for deaf people, who rely on non-auditory sensory information for dancing. In the present study, we investigated beat synchronization to vibrotactile electronic dance music in hearing and deaf people. We tested 78 deaf and 145 hearing individuals on their ability to bounce in time with the tempo of vibrotactile stimuli (no sound) delivered through a vibrating platform. The corresponding auditory stimuli (no vibrations) were used in an additional condition in the hearing group. We collected movement data using a camera-based motion capture system and subjected it to a phase-locking analysis to assess synchronization quality. The vast majority of participants were able to precisely time their bounces to the vibrations, with no difference in performance between the two groups. In addition, we found higher performance for the auditory condition compared to the vibrotactile condition in the hearing group. Our results thus show that accurate tactile-motor synchronization in a dance-like context occurs regardless of auditory experience, though auditory-motor synchronization was is of superior quality.